ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Puspitasari, Amelia Indriani; Virda Susanti; Ananda Mitsa Ghalizha Laksmanta; Cherli Eka Aprillia (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to compare the financial performance of companies listed on the Indonesia Stock Exchange: PT. Adhi Karya Tbk, PT. Jaya Konstruksi Manggala Pratama Tbk, PT. Nusa Raya Cipta Tbk, and PT. Waskita Beton Precast Tbk for the 2019-2021 period using liquidity ratios, activity ratios, solvency ratios, and profitability ratios. The data used is qualitative data with descriptive analysis, namely a research method that aims to describe the actual situation by collecting collecting, managing, presenting, and analyzing the various data found and comparing them with existing theories. The results of the study reveal that there are variations or differences in the financial performance of companies listed on the Indonesia Stock Exchange: PT. Adhi Karya Tbk, PT. Jaya Konstruksi Manggala Pratama Tbk, PT. Nusa Raya Cipta Tbk, and PT. Waskita Beton Precast Tbk for the 2019-2021 period.